Determinants of Production, International Trade Price Index (IHPI) and the Rupiah Exchange Rate on Indonesian Palm Oil Exports in 2007-2021 - Azzahra, Lailatul Maulida; Dzuriyah, Tsaniyatul; Rahati, Yeni Ayu; Andni, Riyan; Muttaqin, Ibnu; Johanna, Anne; Avinash, Buschhaus; Bevoor, Bevoor (Journal International Dakwah and Communication, 2023)
This research is motivated by the export of palm oil from Indonesia to Malaysia where there are inconsistencies in the determinants that affect the value of exports which can be seen from the number of production levels, the international trade price index (IHPI) and the rupiah exchange rate. speed. This shows the need for research. more about palm oil exports. In this study aims to determine, analyze, explain the influence of Indonesian palm oil exports to Malaysia. The type of research used is quantitative research supplemented by data for the period 2007 to 2021 sourced from the Central Bureau of Statistics (BPS). The data analysis technique used in this study is the Multiple Regression test which includes the Classical Assumption Test, and the Hypothesis Test. The results of the two tests show that in terms of production volume, the International Trade Price Index (IHPI) tends to be positive and not significant, while the rupiah exchange rate tends to be negative and not significant. This means that Indonesian palm oil exports to Malaysia have increased and decreased unbalanced, so these export activities require a strategy that can emphasize export figures by providing information to domestic and foreign investors, both private and government agencies, to pay more attention to several governments.